Democrazia e diritti sociali - Giuseppe Acocella (Democrazia e Diritti Sociali, 2019)
The paper analyses the problem of economic and social inequalities in different geographical areas and highlights how the percentage of the poor has increased. If, on the one hand, we are witness- ing the reduction of extreme poverty for large sections of the population, on the other hand, there is a significant increase in the gap between rich and poor. The Author focuses on some political implications of these processes, which require effective measures to combat poverty and redistrib- ute income to ensure a renewed welfare system.